2020
DOI: 10.1002/advs.202002243
|View full text |Cite
|
Sign up to set email alerts
|

Biomass‐Derived Multilayer‐Structured Microparticles for Accelerated Hemostasis and Bone Repair

Abstract: It is very desirable to develop advanced sustainable biomedical materials with superior biosafety and bioactivity for clinical applications. Herein, biomass-derived multilayer-structured absorbable microparticles (MQ x T y) composed of starches and plant polyphenols are readily constructed for the safe and effective treatment of bone defects with intractable bleeding by coating multiple layers of quaternized starch (Q +) and tannic acid onto microporous starch microparticles via facile layer-by-layer assembly.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 38 publications
(55 reference statements)
1
42
0
Order By: Relevance
“…In addition, many studies have demonstrated that multilayer structures can improve the biostability of lipo some formulations and protect the incorporated compounds in their aqueous interior core or within their multilayer mem brane from external destructive conditions such as light, pH, or enzymes, allowing them to be released at designated tar gets. [29][30][31] Therefore, multilayer liposome is an ideal drug delivery carrier for temoporfin. According to previous reports, HSAencapsulated perfluorocarbon (PFC) (HP) not only has a high oxygencarrying capacity but also prevents oxygen leakage.…”
Section: Preparation and Characterization Of C-ml/hpt/omentioning
confidence: 99%
“…In addition, many studies have demonstrated that multilayer structures can improve the biostability of lipo some formulations and protect the incorporated compounds in their aqueous interior core or within their multilayer mem brane from external destructive conditions such as light, pH, or enzymes, allowing them to be released at designated tar gets. [29][30][31] Therefore, multilayer liposome is an ideal drug delivery carrier for temoporfin. According to previous reports, HSAencapsulated perfluorocarbon (PFC) (HP) not only has a high oxygencarrying capacity but also prevents oxygen leakage.…”
Section: Preparation and Characterization Of C-ml/hpt/omentioning
confidence: 99%
“…Characterizations. The chemical structure of CMCh was explored using 1 H and 13 C NMR (INOVA-600, Varian). The chemical shift was reported according to the internal reference of tetramethylsilane (TMS).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Recently, new types of wound dressings including hydrocolloids, sponges, and hydrogels have been developed. Among these materials, hydrogel wound dressings were capable of forming physical barriers and provided a moist environment at wound sites to promote cell proliferation and skin regeneration . The hydrogels were normally prepared by one or several types of gelation mechanisms including covalent bonds and noncovalent bonds like coordination bonds, hydrogen bonds, ionic bonds, and Schiff bases. By replacing steady networks with noncovalent dynamic linkages, the hydrogels could repair the broken network and maintain the mechanical properties without any external stimuli when the structure was destroyed, showing an excellent self-healing property .…”
Section: Introductionmentioning
confidence: 99%
“…The in vivo liver bleeding rat model was employed for hemostasis assay on the basis of previously published research. 71 Details are listed in Supporting Information.…”
Section: ■ Conclusionmentioning
confidence: 99%